TINGKAT KECEMASAN DENGAN NIAT BERTINDAK KUNJUNGAN ULANG PENGGUNAAN KONTRASEPSI DALAM SITUASI PANDEMI COVID-19 - Mega Octamelia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2022)
The coronavirus that causes Coronavirus Disease-2019 (COVID-19) is a new type of virus discovered in humans. The risk of transmitting COVID-19 is very high and causing a pandemic. This causes anxiety in family planning acceptors to come to health care facilities. This anxiety is evidenced by the decrease in injection family planning acceptors from 524,989 to 341,109. Anxiety of family planning acceptors that arises in certain situations, namely COVID-19 can also be called situational anxiety. Symptoms can be characterized by a slight discomfort, palpitations and disorientation. The purpose of this study was to determine the relationship between anxiety levels and intention to act on repeat visits for contraceptive in the COVID-19 pandemic situation. This type of research is analytic with a cross sectional approach. The population in this study were all family planning acceptors who were in the working area of Puskesmas Karang Rejo, Tarakan City in October. The sampling technique in this study used a simple random sample with a number of sample 35 respondents. Bivariate analysistest use Spearman test. The correlation coefficient value is 0.453, the magnitude of the correlation coefficient is positive, which means the less anxiety, the higher intention to act. Spearman test obtained p = 0.006 <0.05. The conclusion is that there is a correlation between the level of anxiety with the intention to act on repeat visits to the use of contraception at the Puskesmas Karang Rejo, Tarakan City.